The effect of tree mortality on CO2 fluxes in an old-growth spruce forest - Karelin, D. V.; Zamolodchikov, D. G.; Shilkin, A. V.; Popov, S. Yu; Kumanyaev, A. S.; de Gerenyu, V. O. Lopes; Tel’nova, N. O.; Gitarskiy, Michael L. (European journal of forest research, 2021)
Long-term (2009–2019) field studies of the CO 2 fluxes over the Valday upland in north-western European Russia were performed in an old-growth spruce-dominated forest subject to the combined effects of climate change, bark beetle attacks and windfall events. The annual carbon uptake within the study area decreased from − 300 g C m −2 yr −1 in 2010–2011 to − 95 g C m −2 yr −1 in 2018 as a result of progressive tree mortality. However, mortality did not cause a significant reduction in specific ecosystem respiration. The respiration of the damaged forest was formed by efflux from soil (64.8%), living vegetation (15.5%), hotspots under dry standing trees (12.1%) and decomposition of woody debris (7.6%). High correlations between net ecosystem exchange and dry standing spruce stocks and average soil CO 2 efflux were found. The decrease in the carbon sink was followed by a decline in evapotranspiration from 0.0142 ± 0.0003 g H 2 O m −2 s −1 for May–October 2010 to 0.0116 ± 0.0002 g H 2 O m −2 s −1 in 2018. We assumed that the decrease in carbon uptake was due to both the reduction in primary tree production and the decrease in the area of the unaffected stands. Our estimates show that an increase in tree mortality up to 27% of a stand area could turn an old-growth spruce forest into a net source of CO 2 . This should be taken into account when considering human-induced and climate-related effects on boreal forests.